Optimization and Application of Ammonia Spraying Device Using Dynamic Matrix Control with Variable Parameters Based on Feed-Forward Loop - Xin XUN; Kai SHENG; Xiangyu CHEN; Jijun DENG (Zhongguo dianli)
Facing the challenges of the controls in the selective catalytic reduction (SCR) flue gas denitration system of thermal power units, such as long duration of time delay, high inertia and strong nonlinearities, typical PID regulator-based ammonia spraying control systems are not capable of meeting the increasingly high control performance and environmental protection requirements. Regarding the existing issues in the conventional regulators, this paper proposes an optimized ammonia spraying control strategy using dynamic matrix control with variable parameters on the basis of feed-forward loop. The new control strategy can speed up the closed-loop control rate through predictive control, alleviate the external disturbance through feed-forward loop and improve the robustness through self-adaptability to variable parameters. At last, an optimized ammonia spraying control device based on the new strategy is developed and then implemented to a 660 MW supercritical unit. The application practice demonstrated the effectiveness of the device in the performance improvement of ammonia spraying controls.